O conceito de povo nos escritos de Maquiavel - Benetti, Fabiana de Jesus (2021)
In chapter IX of The Prince, Machiavelli mentions for the first time a division that exists in all cities between the humors (umori) of the great (grandi) and the people (popolo): a division caused by the opposition between the desire of domination of the great against the desire of non-domination of the people. This statement, which was repeated by the author in Discourses on the First Decade of Titus Livius and in the Florentine Histories, is the starting point for understanding that, for Machiavelli, politics is always marked by the conflict between antagonistic humors. From this perspective, this work is specifically aimed at investigating what characterizes popular humor in Machiavelli's political thought. Our intention is to understand both the meanings that the term people carries in the author's writings, and the place that people occupy in the dynamics of a policy conceived from the perspective of conflict. To approach the theme, we took as a starting point a bibliographical review of authors who, when interpreting Machiavelli's writings, reflected on the role that the Florentine would have reserved for the people in their writings. After the construction of this interpretative panorama, the research is directed to a historical presentation of how the term people is constructed in the context of the politics of Florence from the 12th to the 15th century, the latter being the century in which Machiavelli rose to an administrative position with the government of Florence, beginning his history in the practical and theoretical sphere of politics. This path was a kind of introduction that allowed us to go to Machiavelli's texts in order to reflect on what the author maintains about the people as a specific historical figure and what he adds to the concept of people. The conclusion of our research is that Machiavelli, throughout his texts, completed a political concept of the people, noting that, although marked by certain social determinations and benefits, what gives political identity to the people is the desire that makes them stand out in public life, the desire not to be dominated by the great.